Mobile-based Waste Bank Aplication Design: A Case Study of the Anggrek Sectoral Waste Bank - Pramono, Anang; Muchlasin, Achmad (Pelopor Publikasi Akademika, 2025)
Waste banks are a solution proposed by the government to manage waste collectively and help reduce waste problems. However, over time, several issues have arisen, such as the process of depositing waste by customers who have to bring waste to the waste bank location, manual recording of waste deposit data, and withdrawal of savings balances that still require personal communication with the management. Therefore, an application is needed to address these problems of waste banks. This study aims to design a real-time Android application to overcome these challenges, with a case study on the Anggrek Sectoral Waste Bank in Wiyung District, Surabaya. The development of this application uses the prototype development method. The results show that the application performed successfully in all situations, with a satisfactory level of user satisfaction. This is evidenced by the results of testing using 46 test cases with Black Box Testing and evaluations of 35 respondents using the System Usability Scale questionnaire, which yielded a score of 75. The combination of good functional performance and high satisfaction indicates that this application is ready to be used optimally according to the needs of the waste bank